Molecular Analysis and Phylogenetic Relationship of Filamentous Green Algae - Pithophora roettleri (Roth) Wittrock - D, Nivedha; Banu, H Rehana (Asian Journal of Biological and Life Sciences)
Algae were considered to be the first species that appeared billions of years before plants, which are capable of photosynthesis. Filamentous green algae are characteristic of littoral algal communities which are found to be attached to the substrate or floating aggregations in the freshwater habitats. In small water habitats, these green algae are very common and almost occur everywhere. Most of the algae serve as food for aquatic animals and are also used to manufacture papers and fibres. Hence it possesses good economic value. Pithophora is a species found throughout the world, mainly in tropical and temperate regions. This study aims to authenticate the algae by means of morphological and molecular characterization. The molecular characterization was carried out using partial sequencing of 28S rRNA. The data were interpreted with the BLAST program in the NCBI database, where the sequence of algae revealed the identity matches in the range of 99.59% with the available Pithophora roettleri (MN017042.1) strain recovered from the GenBank.
Keywords: Freshwater; Molecular characterization; Morphology; PCR amplification; Phylogenetic tree; Pithophora